1998
DOI: 10.3109/10826089809069809
|View full text |Cite
|
Sign up to set email alerts
|

Children in the Streets of Brazil: Drug Use, Crime, Violence, and HIV Risks

Abstract: The presence of vast numbers of unsupervised and unprotected children is a phenomenon that is common throughout Latin America, and in few places are the street children more visible, and reviled, than in Brazil. Estimates of their numbers in Brazil have ranged from 7 to 17 million, but more informed assessments suggest that between 7 and 8 million children, ages 5 to 18, live and/or work on the streets of urban Brazil. Accounts of drug abuse among street youths in Brazil are commonplace. Numerous scientific st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 10 publications
2
35
0
Order By: Relevance
“…5 Qualitative studies in Brazil suggest that family breakdown combined with economic problems, peer pressure, and drug use are driving factors towards street life; these studies provide alarming insights into the risks these children face. 6,7 Reports in Peru are similar; a survey of 134 street children in Lima found that 81% admitted alcohol consumption and 92% admitted to using 'terokal', a volatile solvent. 8 These children often survive by working in the informal sector.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…5 Qualitative studies in Brazil suggest that family breakdown combined with economic problems, peer pressure, and drug use are driving factors towards street life; these studies provide alarming insights into the risks these children face. 6,7 Reports in Peru are similar; a survey of 134 street children in Lima found that 81% admitted alcohol consumption and 92% admitted to using 'terokal', a volatile solvent. 8 These children often survive by working in the informal sector.…”
Section: Introductionmentioning
confidence: 95%
“…[4][5][6][7] A study in La Paz, Bolivia, reported that up to 85% were victims of physical abuse, with children also reporting experience of sexual abuse (20%), serious medical conditions (53%), use of alcohol (58%), and inhalation of volatile solvents (88%). 5 Qualitative studies in Brazil suggest that family breakdown combined with economic problems, peer pressure, and drug use are driving factors towards street life; these studies provide alarming insights into the risks these children face.…”
Section: Introductionmentioning
confidence: 99%
“…The primary reasons for detention of youth include petty theft and robbery, although they also are detained for assault and homicide (Tapparelli and Almeida 2003). The existence of this large number of detained children and their unmet social and health needs has become a public health crisis Inciardi and Surratt 1998;Noto et al 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Detained children and adolescents primarily have streetliving circumstances, which is a serious social problem in resource-poor countries such as Brazil (Goodwin et al 2004;Inciardi and Surratt 1998;Lockhart 2002;Tantoco 1993). In Latin America, estimates of the number of children and adolescents living in the streets varies from 100,000 to 30 million (Lejeune 1993), and in Brazil there are no precise population estimates (Abdelgalil et al 2004;Celia et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…4 We anticipated that there may be different pathways into and out of homelessness in the two settings; therefore, we compared newly homeless and experienced youth (those on the streets a long time) in each country. 5 Homeless youth show very high rates of problem behaviors in both countries (Booth & Zhang, 1996;Inciardi & Surratt, 1998;Kipke, Montgomery, Simon, & Iverson, 1997;Sleegers, Spijker, van Limbeek, & van Engeland, 1998;Greene & Ringwalt, 1996;Kral, Molnar, Booth, & Watters, 1997;Rosenthal, Moore, & Buzwell, 1994;Buhrich & Teesson, 1990;Kamieniecki, 2001;Teesson, Hodder, & Buhrich, 2003). Yet, it is unclear whether newly homeless youth in both countries would have exhibited similar behavioral profiles whether they were in the US and AU.…”
Section: Introductionmentioning
confidence: 99%